2019
DOI: 10.2134/agronj2018.10.0653
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and Economic Benefits of Rotating Corn with Soybean and Spring Wheat under Different Tillage in Eastern Canada

Abstract: Agronomic and economic performance of the corn (Zea mays L.)–soybean [Glycine max (L.) Merr.] rotation is well documented, but few studies have investigated the addition of spring wheat (Triticum aestivum L.) to this rotation, particularly at the northern limit of corn and soybean production in North America. A 6‐yr field study was initiated in 1999 on a clay soil in eastern Canada to identify the best crop rotation (continuous corn, continuous soybean, corn–soybean, corn–corn–soybean, corn–soybean–spring whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…Other studies have also reported greater soybean yields in wheat‐containing rotations compared to when rotated only with corn (Katsvairo & Cox, 2000; Kazula & Lauer, 2018). However, other studies have reported that soybean yields in wheat‐containing rotations are similar to when rotated only with corn (Gagnon et al., 2019; Lund et al., 1993).…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Other studies have also reported greater soybean yields in wheat‐containing rotations compared to when rotated only with corn (Katsvairo & Cox, 2000; Kazula & Lauer, 2018). However, other studies have reported that soybean yields in wheat‐containing rotations are similar to when rotated only with corn (Gagnon et al., 2019; Lund et al., 1993).…”
Section: Resultsmentioning
confidence: 89%
“…Straw sales minimized net revenue reductions associated with including wheat in rotations in the RT system at Ridgetown. Other studies have also reported that wheat straw sales enabled wheat‐containing rotations to match, or exceed, economic performance of CS rotations (Gagnon et al., 2019; Katsvairo & Cox, 2000)…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations